The Correspondence of Zwingli and Oecolampadius : Translated and introduced by Nigel Harris and Sharon van Dijk - Harris, Nigel W. (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
The 183 letters which Huldrych Zwingli and Johannes Oecolampadius exchanged between 1522 and 1531 are a major resource for students of the Swiss Reformation. They have, however, been largely neglected because they have hitherto been available only in the original Latin. This volume translates them all into modern English, along with explanatory notes and a substantial introduction. The book as a whole proposes and initiates a significant re-assessment of several aspects of early Reformation history, such as the extent of Oecolampadius's contribution, the precise nature of his relationship with Zwingli, and the strong connections that existed between the reformers of Zürich, Basel and Strasbourg.